Probiotics: A solution to the prevention of antimicrobial resistance - Poh, Chit Laa *; Kanwal, Khalid *; Lim, Hui Xuan * (Academic Press, 2023)
Antibiotics against bacterial infections have been very successful in terms of the amelioration of diseases and the prevention of millions of deaths. However, widespread antibiotic usage has also led to an increased prevalence of antibiotic resistance, which causes debilitating multidrug-resistant infections with huge economic burdens. The use of probiotics offers a promising approach that could lower the risk of contracting bacterial infections and reduce the incidence of antibiotic resistance. There are several mechanisms that would help explain how probiotics might combat bacterial infections and antibiotic resistance. These include the production of bacteriocins which eliminate other pathogenic bacteria through competitive exclusion, production of siderophores, H2O2, and biosurfactants. Probiotics also stabilize the intestinal epithelial barrier, enhance the integrity of mucosal cells, and reduce pathogen mobility. Furthermore, probiotics modulate the immune response by producing anti-inflammatory cytokines such as interleukins, tumor necrosis factors, interferon-γ, transforming growth factors, and chemokines from antigen-presenting cells involved in the immune system. This could result in the reduction of intestinal inflammation, activation of toll-like receptors signaling pathways, and the suppression of proinflammatory cytokine expressions which were observed to lower the incidence of bacterial infections. This chapter evaluates the potential of probiotics in the reduction of the risk of infections caused by bacteria and the prevention of antibiotic resistance, elaborates on the mechanism of probiotic action against bacteria, and how probiotic use could modulate the immune response to confer protection to the host.